2020
DOI: 10.24193/ed21.2020.19.12
|View full text |Cite
|
Sign up to set email alerts
|

Use of Digital Games in Teaching Vocabulary to Young Learners

Abstract: It has been an educational policy for the Turkish educational authorities to teach English as a foreign language from early ages of children. This research attempts to determine the role of digital games on enhancing English vocabulary and to com¬pare games with pen and paper practices. For this purpose, digital games on EBA (Education Informatics Network) platform were used for enhancing vocabulary teaching in a public primary school in Turkey. The study recruited 37 third-grade students from two separate cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…The findings of the current study are in line with Hazar [42], who examined the impact of using digital games on promoting Turkish EFL learners' vocabulary learning. His findings demonstrated that the EG outperformed the CG in the posttest, with significant statistical results.…”
Section: Discussionsupporting
confidence: 86%
“…The findings of the current study are in line with Hazar [42], who examined the impact of using digital games on promoting Turkish EFL learners' vocabulary learning. His findings demonstrated that the EG outperformed the CG in the posttest, with significant statistical results.…”
Section: Discussionsupporting
confidence: 86%
“…The qualitative analysis brought to light aspects concerning how the students' ideas generated the possibility of facial, vocal, or gesture recognition to solve everyday 3.4. Interdisciplinary Perspectives for studying digital citizenship Most of the reviewed studies present the approach of language and communication contents alongside those specific to digital citizenship (Anderson, 2018;Germeroth, Kelleman & Spartz, 2018;Hazar, 2020;Gezer & Anilan, 2021;Șahin & Gül Özenç, 2021). On the other hand, the integration of mathematics-specific content alongside digital content is the second trend noted in the studies reviewed (Higgins, Crawford, Huscroft-D'Angelo & Horney, 2016;Anderson-Pence, Tygret & Crocker, 2020;Ökördi & Molnár, 2022).…”
Section: Teaching Methods and Learning Tasks Specific To Digital Citi...mentioning
confidence: 99%
“…Thus, DGBELL focuses on vocabulary as one of the competencies. A number of 12 studies conducted to identify the effects of digital games in improving the English vocabulary acquisition (Chen & Hsu, 2019;Chandra & Kepirianto, 2021;Sagubay-Lozarito & Segumpan, 2022;Padar, 2022;Vásquez & Ovalle, 2019;Pahamzah et al, 2020;Tan et al, 2019;Guaqueta & Castro-Garces, 2018;Vélez-Agosto & Rivas-Vélez, 2018;Hazar, 2020). Based on the study by Vásquez and Ovalle ( 2019), an evaluation of the findings acquired from the vocabulary assessment, learners' and educators' records revealed that following the intervention of a digital game on English vocabulary, the learners could acquire a considerable amount of vocabulary.…”
Section: Impacts Of Dgbell In Regard To Cognition Outcomes (Language ...mentioning
confidence: 99%